Technological, Pedagogical and Content Knowledge (TPACK) of Agriculture Teachers: Basis for Mentorship Program - Catherine P. Loseñara; Jleian Mard Loseñara; Ryan A. Jore (The Asian Journal of Technology Management (AJTM), 2025)
Abstract. Education continuously undergoes transformation driven by evolving teaching-learning settings and paradigm shifts. The COVID-19 pandemic accelerated the adoption of various educational modalities, including online and flexible learning systems. Despite widespread use of technology in education, limited research has examined the technological, pedagogical, and content knowledge (TPACK) of agriculture teachers who face unique challenges due to specialized content and limited pedagogical training. This study addresses this gap by assessing the TPACK competencies of agriculture instructors at a College of Agriculture, where many lack formal teaching education. Using an adapted TPACK instrument, a descriptive quantitative design revealed that teachers perceived their Content Knowledge (CK) as fair, while perceiving moderate competence in Technology Knowledge (TK) and Technological Content Knowledge (TCK). These findings inform the design of a targeted mentorship program to support agriculture teachers in integrating technology effectively into their teaching. The study further revealed strong interrelationships among TPACK constructs, underscoring the integrated nature of technological, pedagogical, and content knowledge essential for effective technology integration in agriculture education.  Keywords: Technology, educational technology, agriculture, mentorship program, online education, TPACK